Republic of Latvia : Second Review and Financing Assurances Review Under the Stand-By Arrangement, Request for Extension of the Arrangement and Rephasing of Purchases Under the Arrangement and Request for Waiver of Nonobservance and Applicability of Performance Criteria. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
This paper discusses key findings of the Second Review and Financing Assurances Review Under the Stand-By Arrangement for Latvia. The sharp economic downturn is starting to bottom out, although recovery has not yet begun. The authorities have implemented the June 2009 supplementary budget, and met with a wide margin the end-September performance criterion on the adjusted primary balance. The continuous performance criterion on external payments arrears was missed by a small amount, which the authorities expect to resolve soon.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet